Legal Analysis of The Responsibility of Flat House Developers in Fulfilling The Sales Purchase Binding Agreement (PPJB) As Reviewed From Law No. 20 of 2011 Concerning Flat Houses - Tobing, Sentiana Br. Lumban; Simamora, Janpatar; Siregar, Ria Juliana (Journal of Law, Politic and Humanities, 2026)
This research is conducted to examine the juridical aspects construction of developers’ liability in the implementation of Sale and Purchase Binding Agreements (PPJB) for apartment units under Law Number 20 of 2011 on Flats, as well as the mechanisms for resolving consumer disputes. This research applies a doctrinal legal framework grounded in legislation, legal theory, and judicial decisions legislation, scholarly literature, and the Decision of the Yogyakarta High Court Number 91/PDT/2020/PTYYK as analytical materials. The findings indicate that developers’ liability forms a multi-layered liability system encompassing administrative, criminal, and civil responsibility. However, in practice, enforcement is predominantly pursued through breach of contract claims under the Civil Code, while administrative and criminal sanctions have not been optimally implemented. This reflects a gap between normative provisions and practical enforcement. The study concludes that developers’ liability demonstrates a hybrid liability character, combining contractual and public regulatory responsibility, thereby requiring stronger supervision and consistent law enforcement to ensure consumer protection and legal certainty.